Effects of virtual reality on gait and balance in patients with Parkinson's disease: A systematic review - Palop-Montoro, María Victoria; Cremades-Santiago, María de las Nieves; Ruiz-López, Inmaculada; León Garzón, Martha Cecilia (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Parkinson's disease causes a high level of motor and functional disability. New virtual reality techniques can improve the symptoms of these patients. This study aimed to know the effects of virtual reality on gait and balance in patients with Parkinson's, as well as to describe the virtual reality techniques and the tools used to measure these variables in this pathology. A systematic review was carried out following the PRISMA regulations. The databases used were PubMed/Medline, LILACS and IBECS, Cochrane Library, CINAHL, Sport Discus, Psycinfo and Web of Science. The last search was carried out in May 2023. A total of 8 studies are part of this review and demonstrate that patients with Parkinson's can improve balance and gait using different virtual reality modalities such as the Wii Fit and Xbox 360 video game consoles. The most used tools to measure balance were Sensory Organization Test and Berg Balance Scale, and those to measure gait were Timed Up and Go and Dynamic Gait Index. Virtual reality as a therapy improves gait and balance in patients with Parkinson's and no adverse effects are shown after its use.